Prevalence of under-five years of age mortality by infectious diseases in West African region - Yusupha Sanyang (Elsevier, 2019)
Background: The under-five mortality is one of the indicators of the progress and improvement of the health system of a country. With the passage of the Millennium Development Goals and now four years into the sustainable development goal the countries within West Africa still are faced with the high burden of under-five mortality especially from infectious diseases. Objective: The objective of this review is to highlight the prevalence of under-five mortality in West Africa. Data sources: This is a grey literature review of under-five deaths in West Africa. Searches for relevant literatures was made on pub Med, Google Scholar and Scopus. Searches was also done in institute for Health Metrics and Evaluation (IHME) and World Health Organization Data Bases. Relevant publications and reports available at WHO and UNICEF websites were also used. A total of ten articles were included in this review and the rest are publications from UNICEF AND WHO. The keywords used during the search include under-five mortality, infectious diseases, and West Africa. The year of publication of the reports and data included in this review ranges from 2015 to 2017. Results: There is still high burden of under-five mortality in the West African region and the major contributing factor is the infectious diseases including Pneumonia Sepsis tetanus Diarrhoea Malaria AIDS measles meningitis. While others are still lingering, it was only Niger and Senegal that had achieved the millennium development goal target of reducing under-five mortality to two-thirds from m1990-2015. However, Cape Verde has now achieved the SDG target 3.2 with an under-five mortality of 17/1000 live births. Conclusion: The countries in this region needs to work hard to reduce this burden. This requires huge investment especially the financial and human resource development. Keywords: Infant, Mortality, Infectious disease, Children, Under-five, West Africa